Material and flow engineering approach in improving the membrane distillation process - Tan, Yong Zen (2019)
Membrane distillation (MD) is a thermally-driven process involves distillation through a microporous hydrophobic membrane, which acts as a physical interface between the hot feed and cool permeate. Despite being a promising easy to integrate, low-cost, energy-saving alternative to conventional separation processes like distillation and reverse osmosis (RO), MD have not gained much commercial attention due to low fluxes or output per unit energy and pore-wetting problems, limiting its uses to desalination and tertiary wastewater treatment. In view of the problems which plagues the MD process, a series of research were carried out to understand the underlying mechanisms contributing to the problems and investigate the various proposed solutions through a two-pronged approach to the problem.